Glazing effect for producing environmentally friendly ceramics for cladding applications: Technical paper - Pavlycheva, Elizaveta; Pikalov, Evgeniy; Selivanov, Oleg (HEMIJSKA INDUSTRIJA (Chemical Industry), 2021)
This paper presents results of comparative studies of environmental safety of ceramic materials, based on a low-plasticity clay with the introduction of galvanic sludge, boric acid and titanium dioxide in 3 different combinations. The experimental samples were manufactured under 15 MPa pressing pressure and at the maximum firing temperature of 1050 oC. Prior to the toxicological experiments, diurnal extracts of the materials into the model neutral and acidic media were obtained. The toxicological safety was determined by using the Daphnia mortality method, and by comparing the maximum permissible concentrations of heavy metals for drinking and household water with the heavy metals concentrations in diurnal extracts. The presented data show that the combined introduction of all the investigated additives results in the glazing effect of ceramic particles surfaces so that an environmentally safe material can be produced that exhibits sufficiently high-performance properties. The use of low-plastic clay and electroplating sludge expands the raw material base for producing ceramics and allows the disposal of environmentally hazardous compounds of heavy metals contained in electroplating sludge. Ceramic materials based on the developed charge composition can be used for producing items for external cladding for buildings and structures.